Optimizing Immunostaining of Enamel Matrix: Application of Sudan Black B and Minimization of False Positives from Normal Sera and IgGs - Yang, Xu; Vidunas, Alexander J.; Beniash, Elia (Frontiers in Physiology, 2017)
Non-specific fluorescence from demineralized enamel matrix can significantly compromise the immunofluorescence studies and lead to false positives. Our goal was to assess degrees of nonspecific binding under different conditions and try to optimize procedures for immunofluorescence studies of forming enamel. Firstly, we compared two methods for background fluorescence elimination, i.e. sodium borohydride and Sudan Black B treatments. The results demonstrated that Sudan Black B is far superior to sodium borohydride in reducing the background fluorescence in dental tissues. We also studied the extent of non-specific binding of normal sera and purified polyclonal immunoglobulins (IgG) from five mammalian species, guinea pig, rat, rabbit, goat and sheep, over a broad range of dilutions. For all sera tested fluorescence signals increased exponentially from 1:1000 to 1:100. Interestingly, the nonspecific binding of sera from rodent species was below that of positive control in the whole range of dilutions. In contrast, incubation with sera from 3 non-rodent species produced much higher signals which surpassed the positive control signal at 1:250 1:500 dilution range. Most of the IgGs didn’t show significant non-specific binding within 0.25-5 µg/ml range, except rabbit IgG which demonstrated extremely high affinity to the enamel matrix even at concentrations as low as 1 µg/ml. Further studies confirmed that Fab fragments of purified normal rabbit IgG, not conserved Fc fragments, were involved in the interactions. Our observations suggest this high affinity is associated with the antigen binding sites of rabbit IgG. We anticipate that our results will help enamel researchers to optimize and standardize their immunochemical procedures.